Enriching student knowledge on sustainable forest management practices by forestry professionals: a look into the generic structure potential for Malaysian forestry annual reports / Wan Farah Wani Wan Fakhruddin … [et al.] - Wan Fakhruddin, Wan Farah Wani; Saidalvi, Aminabibi; Hassan, Hanita; Hanafi Zaid, Yasmin (Akademi Pengajian Bahasa, 2021)
Despite the establishment of numerous goals related to sustainable forest management (SFM) including the setting of Goal 15 in the 2015 United Nations’ Sustainable Development Goals (SDGs), to date, its implementation is seen to be problematic. Its poor implementation is often associated with ineffective management of forests areas, which poses some challenges for students to gain a better understanding of the nature of forestry professions and the expectations that come along with the responsibility of sustainably managing forest reserves and lands. This study aims to explore how forestry-related agendas are conveyed in the Year under Review section of the Malaysian forestry annual reports (FAR) issued by the Forestry Department of Peninsular Malaysia (FDPM) from a systemic functional linguistics perspective. As one of the government agencies that has been given the mandate to protect and manage 4.8 million hectares of forest areas in Peninsular Malaysia, analysing the practices and agendas conveyed in FAR is deemed to be indispensable especially for forestry students who wish to develop a better understanding of the forestry profession upon their study completion. This study sets out to identify the generic structure potential for the Year under Review section of FAR throughout ten years (2009 – 2018) which reveals the relationship between the genre of FAR and its context. The Generic Structure Potential (GSP) model proposed by Halliday and Hasan (1996) is adopted in this study to identify the obligatory and optional elements included in FAR as well as the functions of each element observed in the Year under Review section of FAR. The results of the study show that eleven obligatory elements constitute the generic structure of the Year under Review section of FAR which are directly related to the ideal SFM practices that contribute to SDG Goal 15 (Protect, restore and promote sustainable use of terrestrial ecosystems, sustainably manage forests, combat desertification, and halt and reverse land degradation and halt biodiversity loss). The establishment of the generic structure potential for Year under Review section of Malaysian Forestry Annual Report will help undergraduate forestry students to understand the actual practices in the forestry profession to equip them with knowledge in real-life settings.